Shortchanged : life and debt in the fringe economy - Karger, Howard Jacob, 1948- (BK currents book., 2005)
Drive through just about any low-income neighborhood and you're sure to see streets lined with pawnshops, check cashers, rent-to-own stores, payday and tax refund lenders, auto title pawns, and buy-here-pay-here used car lots. We're awash in "alternative financial services" directed at the poor and those with credit problems. Howard Karger describes this world as an economic Wild West, where just about any financial scheme that's not patently illegal is tolerated. Taking a hard look at this fringe economy, Karger shows that what seem to be small, independent storefront operations are actually page